Comparative efficacy of two Ivermectin Pour-on anthelmintics in beef steers in a commercial feedyard - Tarpoff, A.J.; Guichon, T.; Thomson, Daniel U.; Wileman, Benjamin W.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Generic products generally have a cost advantage for beef producers over brand-name products. Recently, many beef producers have debated whether to utilize generic anthelmintics in cow/calf herds and feeder cattle. If generics are to be justified, the products must be proven to have efficacy similar to the brand-name product. Previous studies have indicated that generic macrocyclic lactones are less effective in controlling gastrointestinal parasites of cattle than the original brand-name products. The objective of this study was to compare the efficacy of Vetrimec (Norbrook Laboratories Limited, Newry, Co. Down, Northern Ireland) pour-on and Ivomec (Merial Animal Health, Duluth, GA) pour-on by utilizing the fecal egg reduction test in newly arrived feedlot steers.
Keywords: Beef; Ivermectin Pour-on; Feedlot; Anthelmintics